2016
DOI: 10.1089/ars.2015.6498
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) Improves Liver Fibrosis by Regulating the NLRP3 Inflammasome via Redox Balance Modulation

Abstract: Ang-(1-7) improved liver fibrosis by regulating NLRP3 inflammasome activation induced by Ang II-mediated ROS via redox balance modulation. Antioxid. Redox Signal. 24, 795-812.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
76
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 36 publications
8
76
0
Order By: Relevance
“…As for signal 2, we show for the first time that ROS generation and lysosome stability regulate Ang II activation of the NLRP3 inflammasome and effectuate the macrophage bacteria killing function. Similarly, a recent study demonstrated that the NLRP3 inflammasome is activated by Ang II via the Toll-like receptor 4 (TLR4)/MyD88/NF-κB pathway in hepatic fibrosis [37]. Nonetheless, our data imply that lysosome stability controls the NLRP3 inflammasome activation and functionality in response to Ang II in macrophages (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…As for signal 2, we show for the first time that ROS generation and lysosome stability regulate Ang II activation of the NLRP3 inflammasome and effectuate the macrophage bacteria killing function. Similarly, a recent study demonstrated that the NLRP3 inflammasome is activated by Ang II via the Toll-like receptor 4 (TLR4)/MyD88/NF-κB pathway in hepatic fibrosis [37]. Nonetheless, our data imply that lysosome stability controls the NLRP3 inflammasome activation and functionality in response to Ang II in macrophages (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Our previous study (4) further confirmed that Ang II enhanced NOX4-derived ROS production in HSCs, leading to NLRP3 inflammasome activation and resultant collagen synthesis.…”
Section: Introductionsupporting
confidence: 67%
“…Ang-(1–7) protected against BDL- and AngII-induced liver fibrosis and inhibited expression of mir-21 . The principal findings obtained include the following: (1) mir-21 is positively correlated with liver fibrosis and oxidation; (2) both ERK/NF-κB and Smad3/NOX/ROS pathways mediate AngII-induced overexpression of mir-21 ; (3) mir-21 activates the ERK/NF-κB and Smad2/3/NOX4/ROS pathways in HSCs via targeting Spry1, Smad7 for degradation, respectively; (4) AngII activated NLRP3 inflammasome/IL-1β axis and thus promoted HSC activation via the mir-21 /Spry1/ERK/NF-κB and mir-21 /Smad7/Smad2/3/NOX4 pathway, respectively; and (5) Ang-(1–7) protected against BDL- or AngII-induced liver fibrosis and inhibited mir-21 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated that Ang-(1-7)/Mas axis prevented the rise of ROS levels induced by TGF-β1 in C 2 C 12 myotubes. These results concur with previous evidence indicating that Ang-(1-7) via the Mas receptor decreases oxidative stress in different cell types, such as adipocytes [49], cerebral endothelial cells [50], and, interestingly, in pathologies associated with skeletal muscle atrophy such as diabetes [51], cardiac failure [52], and hepatic damage [53]. Additionally, previously published results by us shows that Ang-(1-7)/Mas receptor prevents ROS induction by Ang-II in skeletal muscle cells [54].…”
Section: Discussionsupporting
confidence: 92%